MOTIF NGECENG DI KALANGAN REMAJA (Studi Perilaku Menyimpang Kehidupan Remaja Di Nagari Lingkuang Aua Simpang Ampek Kabupaten Pasaman Barat) - Yeni, Melihazmi - (Pendidikan Sosiologi, 2014)
Adolescence is a period of adjustment to the environment around it, particularly with the order of the norms, values, customs, and ethics in society. At the time of this adjustment often leads to various problems such deviant behavior. So does that happen in Nagari Lingkuang Aua Simpang Ampek found that adolescents often do activities that violate traffic norms as reckless, ngetrek or ngedrift. This activity is called the ngeceng drive, this activity is carried out by young people in groups. The theory used in this study is a phenomenological theory developed by Alfred Schutz. As this study used a qualitative approach which is defined as understanding perceived by others, understand the mindset and the other persons perspective. Of the studies that have been conducted, it was found that the forms of activity undertaken by adolescent ngeceng is showing the ability and agility to drive a vehicle like ngetrek or ngedrift and inconsiderate, but it also consume teen drinking alcoholic beverages such as wine and comes with some pot (marijuana), among adolescents also make ngeceng as a venue to find a girlfriend. While the motive teen ngeceng activity in the 32 Simpang Ampek this is the desire of adolescents to find opponents and gain prestige from the other groups, search perhatian dan mental combat with the police in order pengeceng regarded as brave and to remove the whole night and boredom as well as serve as a hobby which leads them to frequently perform these activities.